Pengaruh Pelatihan, Disiplin dan Motivasi Kerja Terhadap Kinerja Pegawai PT.Bank Mega Tbk - Ivan Faizal (LP2M CBI PRESS, 2017)
Effect of job training (X1), labor discipline (X2), and motivation (X3) jointly to employee performance (Y) is shown by the value of the regression of X1,X2, and X3 on Y r=0.944, meaning that the effect of the training labor (X1), labor discipline (X2), and motivation (X3)on employee peformance (Y) is very strong, and its influence + (positive) meaning that the higher the job training (X1), labor discipline (X2), and work motivation (X3) then job also increase the performance of an employee (Y) at PT. Bank Mega Tbk. Keywords: Job Training, Labor discipline, Motivation, Ferfomance